Astrocytes detect and upregulate transmission at inhibitory synapses of somatostatin interneurons onto pyramidal cells. Issue 1 (December 2018) - Matos, Marco; Bosson, Anthony; Riebe, Ilse; Reynell, Clare; Vallée, Joanne; Laplante, Isabel; Panatier, Aude; Robitaille, Richard; Lacaille, Jean-Claude
Abstract Astrocytes are important regulators of excitatory synaptic networks. However, astrocytes regulation of inhibitory synaptic systems remains ill defined. This is particularly relevant since GABAergic interneurons regulate the activity of excitatory cells and shape network function. To address this issue, we combined optogenetics and pharmacological approaches, two-photon confocal imaging and whole-cell recordings to specifically activate hippocampal somatostatin or paravalbumin-expressing interneurons (SOM-INs or PV-INs), while monitoring inhibitory synaptic currents in pyramidal cells and Ca2+ responses in astrocytes. We found that astrocytes detect SOM-IN synaptic activity via GABAB R and GAT-3-dependent Ca2+ signaling mechanisms, the latter triggering the release of ATP. In turn, ATP is converted into adenosine, activating A1 Rs and upregulating SOM-IN synaptic inhibition of pyramidal cells, but not PV-IN inhibition. Our findings uncover functional interactions between a specific subpopulation of interneurons, astrocytes and pyramidal cells, involved in positive feedback autoregulation of dendritic inhibition of pyramidal cells. Astrocytes have been shown to regulate glutamatergic transmission in the brain. Here, the authors show that astrocytes also detect and modulate GABAergic transmission from somatostatin but not parvalbumin-positive interneurons, thus regulating dendritic inhibition via a feedback loop.